Characteristic Muscle Quality Parameters of Male Largemouth Bass (Micropterus salmoides) Distinguished from Female and Physiological Variations Revealed by Transcriptome Profiling - Qingchun Wang; Siqi Lu; Yifan Tao; Jixiang Hua; Yan Zhuge; Wenhua Chen; Jun Qiang (Biology)
Male largemouth bass (Micropterus salmoides) are often overlooked because females grow faster. We explored the value of male largemouth bass by comparing muscle nutrition, texture, and transcriptomes between males and females. Females grew faster than males (p < 0.05) because of lipid accumulation. Male fish muscles had higher contents of serine, valine, methionine, arginine, nervonic acid, and α-linolenic acid (p < 0.05), and female fish muscles had higher contents of aspartic acid, glycine, cysteine, leucine, palmitic acid, docosahexaenoic acid, and 11,14,17-eicosatrienoic acid (p < 0.05). Male muscles had a higher concentration of collagen fibers and greater shear force, indicative of a chewier texture. Male muscles had a lighter color, suggesting that they were less susceptible to oxidation and deterioration. Transcriptomic analyses revealed upregulation of lpl, sadb, dgat2, bhmt, tecrb, and hsd3b7, encoding components of amino acid and fatty acid metabolism; and upregulation of akt2, src, and kras, encoding crucial regulators of cellular immunity and homeostasis, in male muscles. Immunity-related pathways, including apoptosis, ErbB signaling, and cellular senescence, were enriched in male fish muscles, indicating heightened immune function. The muscles of male fish have a unique profile and distinctive advantages in terms of nutrition, flavor, texture, and transcriptional regulation.